Functional outcomes in the Cleft Care UK study – Part 3: oral health and audiology. (November 2015) - Smallridge, J.; Hall, A. J.; Chorbachi, R.; Parfect, V.; Persson, M.; Ireland, A. J.; Wills, A. K.; Ness, A. R.; Sandy, J. R.
Structured Abstract: Objectives: To compare oral health and hearing outcomes from the Clinical Standards Advisory Group (CSAG, 1998) and the Cleft Care UK (CCUK, 2013) studies. Setting and sample population: Two UK‐based cross‐sectional studies of 5‐year‐olds born with non‐syndromic unilateral cleft lip and palate undertaken 15 years apart. CSAG children were treated in a dispersed model of care with low‐volume operators. CCUK children were treated in a centralized, high volume operator system. Materials and methods: Oral health data were collected using a standardized proforma. Hearing was assessed using pure tone audiometry and middle ear status by otoscopy and tympanometry. ENT and hearing history were collected from medical notes and parental report. Results: Oral health was assessed in 264 of 268 children (98.5%). The mean dmft was 2.3, 48% were caries free, and 44.7% had untreated caries. There was no evidence this had changed since the CSAG survey. Oral hygiene was generally good, 96% were enrolled with a dentist. Audiology was assessed in 227 of 268 children (84.7%). Forty‐three per cent of children received at least one set of grommets – a 17.6% reduction compared to CSAG. Abnormal middle ear status was apparent in 50.7% of children. There was no change in hearing levels, but more children with hearing loss were managed with hearing aids. Conclusions: Outcomes for dental caries and hearing were no better in CCUK than in CSAG, although there was reduced use of grommets and increased use of hearing aids. The service specifications and recommendations should be scrutinized and implemented.